The Gerald S. Doyle Songsters and the Politics of Newfoundland Folksong - Rosenberg, Neil (Ethnologies, 1991)
The textual contents of the first two editions of St.John’s businessman Doyle’s widely distributed booklets are examined. The focus is upon their relation to political and social ideas and events. In each edition, Doyle printed songs from Newfoundland’s past as a commentary on its present, choosing those which best represented his own perspective. Today a significant number of these songs are still recognized as central to the canon of Newfoundland folksong.